2022
DOI: 10.1021/acs.macromol.2c00343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prereserved Shish Crystals on the Structural Evolution of Ultrahigh-Molecular Weight Polyethylene Films during the Hot Stretching Process

Abstract: Prereserved shish crystals and their influence on the macroscopic properties and structural evolution of ultrahigh-molecular weight polyethylene (UHMWPE) films during the hot stretching process were studied by in situ small-angle X-ray scattering (SAXS)/ultrasmall-angle X-ray scattering (USAXS)/wide-angle X-ray diffraction (WAXD) measurements and ex situ differential scanning calorimetry (DSC) and scanning electron microscopy (SEM) measurements. The SEM result that the fibrous crystals in UHMWPE powder induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 50 publications
0
15
1
Order By: Relevance
“…Mechanical properties such as impact toughness were then associated with the crystalline orientation. 2 Several studies have been using small-and wide-angle X-ray scattering (SAXS/WAXS), 3 often in combination with other techniques such as scanning electron microscopy (SEM), 4 differential scanning calorimetry (DSC), 5 and mechanical testing 6,7 or a combination of them 8 in order to get an indepth understanding of the hierarchical structures in injectionmolded polymers. It has been shown that the skin layers, where the shear and cooling rates are high, often consist of so-called shish-kebab structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mechanical properties such as impact toughness were then associated with the crystalline orientation. 2 Several studies have been using small-and wide-angle X-ray scattering (SAXS/WAXS), 3 often in combination with other techniques such as scanning electron microscopy (SEM), 4 differential scanning calorimetry (DSC), 5 and mechanical testing 6,7 or a combination of them 8 in order to get an indepth understanding of the hierarchical structures in injectionmolded polymers. It has been shown that the skin layers, where the shear and cooling rates are high, often consist of so-called shish-kebab structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A bundle of sample was placed on a sample holder with the fiber direction perpendicular to the x‐ray beam. Standard calculations for a long period ( L M ), lamellar diameter ( L E ), lamellar thickness ( L N ), and the lamellar tilting angle ( 𝜙 ) were conducted using X‐polar software (Precision Works Inc., NY, USA) with reference to previously reported literature 1,32–36 …”
Section: Methodsmentioning
confidence: 99%
“…Standard calculations for a long period (L M ), lamellar diameter (L E ), lamellar thickness (L N ), and the lamellar tilting angle (ϕ) were conducted using X-polar software (Precision Works Inc., NY, USA) with reference to previously reported literature. 1,[32][33][34][35][36] 3 | RESULTIS AND DISCUSSION…”
Section: Small-angle X-ray Scattering (Saxs)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, such research remains at the laboratory stage and has not yet met the requirements for industrial production. Currently, industrial and commercial UHMWPE resins still exist in a highly entangled state, resulting in high melt viscosity, poor flowability, and difficulties in processing and shaping during manufacturing. ,, To overcome this challenge, methods like blend modification, , gel spinning, and compression molding , have been developed for UHMWPE processing. Among these, compression molding stands out as a nonflow processing method that largely reduces the limitations of poor UHMWPE flowability, making it one of the most straightforward processing techniques available .…”
Section: Introductionmentioning
confidence: 99%